URBAN POLICY IN PRACTICE - Tim Blackman London and (Taylor & Francis e-Library, 2003)
In writing this book I have sought to bring together an academic interest in urban policy with the experience of working in a large metropolitan local authority and putting policy into practice. The book draws on both the academic and professional literature for examples and analysis. However, I have subjected this literature to my own ‘litmus test’: does it make sense in terms of real-life policy-making and implementation? The result, I hope, is an account which will give students an academic knowledge of the field. But my intention is to add to this the type of practical understanding which students will need if they move into careers in the public sector, or in the growing number of private companies with professionals working on public sector contracts. The book reflects three particular interests. The first is an emphasis on corporate policy, reflecting my own position as the head of a research unit involved with all the departments and many of the professions of a metropolitan council, as well as parts of the local public sector. I have therefore focused on a series of corporate policy areas: the overall scope and purposes of urban policy, strategic approaches to making and implementing policy, need assessment and the allocation of resources, business planning in the public sector and assuring the quality of services, community development, the carrying out and use of research, the improvement of education and training, the development of local economies, public health, and sustainable development. These areas cut across professional and disciplinary boundaries. I believe this perspective reflects an emerging trend being brought about by an emphasis on outcomes—such as healthy cities and sustainable economic growth—rather than just inputs to urban policy. Such an interdisciplinary approach will not be new to social scientists working in the academic sector. The second interest arises from my role as a local authority research manager. Not only does the book reflect my belief that policy-makers and service managers need to make greater use of research, but it also reflects my conversion to management!